2019
DOI: 10.18502/kss.v3i13.4207
|View full text |Cite
|
Sign up to set email alerts
|

Customer Preferences in Selecting the Pawn Transaction in Pegadaian Syariah Padasuka

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…From the explanation of customer satisfaction above, it can be concluded that customer satisfaction is the rate of a one's pleasure from his comparison of his expectations on a product and what he obtains from that product or service. If one intends to maintain customer loyalty, good facilities and services are needed to make customers feel safe and comfortable (Dwihapsari et al, 2019). The effect of Muslim tourists' perceived value on revisit intention through customer satisfaction is evidenced by Eid (2015), Eid and El-Gohary (2015) and Wiratini et al (2018).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…From the explanation of customer satisfaction above, it can be concluded that customer satisfaction is the rate of a one's pleasure from his comparison of his expectations on a product and what he obtains from that product or service. If one intends to maintain customer loyalty, good facilities and services are needed to make customers feel safe and comfortable (Dwihapsari et al, 2019). The effect of Muslim tourists' perceived value on revisit intention through customer satisfaction is evidenced by Eid (2015), Eid and El-Gohary (2015) and Wiratini et al (2018).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Based on the literature year related to sharia pawnshops for the 2015-2020 period, the following results were obtained : 1) 2015 : 5 literature (Muthmainah & Cholil, 2015), (Irfan, 2015), (Mahmudahningtyas, 2015), (Hadijah, 2015), (Panjaitan, 2015) 2) 2016 : 4 literature (Wandira, 2016), (Suharja, 2016), (Putri, 2016), (Nasution, 2016) 3) 2017 : 6 literature (Anggadini, 2017), (Marhani, 2017), (Wahab, 2017), (Budiman et al, 2017), (Habibah, 2017), (Rukmanasari, 2017) 4) 2018 : 2 literature (Surepno, 2018), (Luluk Wahyu Roficoh, 2018) 5) 2019 : 13 literature Afdhila, 2019;Dwihapsari et al, 2019;Ellysa & Hidayah, 2019;Fedro et al, 2019;Harahap, 2019;Karnawijaya, 2019;Manahaar, 2019;Perwasih, 2019;Pramudya, 2019;Sari, 2019;Sinambela, 2019;Ulwiyah & Dwi Ayuningtyas, 2019) 6) 2020 : 8 literature (Armiya et al, 2020;Hidayat & Zulhelmy, 2020;Kaddi et al, 2020;Muhsin & Masse, 2020;Rahmawati & Mutmainah, 2020;Saputri & Dewi, 2020;Setyaningrum & Khotijah, 2020;Tulasmi & Mukti, 2020) This can be explained in the following From the table, it can be described as follows:…”
Section: A Literature Yearmentioning
confidence: 99%
“…Although many Islamic financial institutions have sprung up in Indonesia, Islamic pawnshops seem to have a special attraction for the community to meet their needs. (Dwihapsari et al, 2019) Practically speaking, sharia pawnshops are also a solution for people who experience financial constraints, who do not have access to banking. (Hidayat & Zulhelmy, 2020) Aghniya Jurnal Ekonomi Islam ISSN 2656-5633 (Online) Vol.04 Nomor 01 Juli 2022…”
Section: Introductionmentioning
confidence: 99%
“…Pawnshop is a non-bank state-owned enterprise that plays a role in distributing financing services, both sharia and conventional pawn systems [1]. The presence of sharia pawnshops is a renewal in pawnshops through rahn financing.…”
Section: Introductionmentioning
confidence: 99%